DEVELOPING THEMATIC ENGLISH VIDEO LEARNING FOR STUDENTS OF PRIMARY SCHOOL TEACHER EDUCATION STUDY PROGRAM IN JAMBI UNIVERSITY - Lovina Choirunisa (Universitas Jambi, 2018)
Lovina (2019) Developing Thematic English Video Learning for Students of Primary School Teacher Education Study Program in Jambi University. Thesis, English Study Program. Faculty of Teacher Training and Education, Jambi University in Academic Year 2018/2019. First Supervisor: Drs. Saharudin, M.Ed.,M.App.Sc.Ph.D. and Second Supervisor: Masbirorotni, S.Pd, M.Sc, Ed. Keywords: Developing, Media Learning, English Video learning, Thematic, Research and Development This study is aimed to describe the process of developing thematic English video learning for students of primary school teacher education study program in Jambi University also to complete the thematic English textbook made by Nurul Hikmah “My Earth”. Here, researcher using ADDIE model to develop the video learning. There are 4 stages that researcher conducted. First is analyze: 1) analyze media, 2) students’ needs, 3) material analysis. Second is design: script and storyboard creation, third is development: media creation, product revision and the fourth is evaluation: formative and summative (validation from the media expert). The participations of this study were second semester students of PSTE program in Jambi University. The participation consists of 120 students of four classes. The result of the study showed that: 1) The developing thematic English video learning is validated by media expert categorized as good and can be try out to the students of PSTE program. 2). This video learning can be used as a guide for lecturers and students in the learning process in class for face-to-face learning with the guidance of the teacher (as facilitator) and independent learning where students can do the exercises, questions and tasks contained in this video learning alone or with friends outside of the class.